The Role of Family Curriculum in Strengthening Student Character: Pre and Post Covid-19 Pandemic - Umi Muzayanah; Faidus Sa’ad (Universitas Negeri Semarang, 2023)
Creating a young generation with noble character is the goal of national education, which is a shared responsibility between schools, families, and communities. Strengthening character in children is important to keep up with the pace of technology and information development, which has a negative impact on the development of children's attitudes and character. The article departs from research that aims to describe the form of integration of the school curriculum and family curriculum as an optimization of the family's role in strengthening student character. Using qualitative methods, the research was conducted in three junior high schools located in urban areas, namely SMPIT Al-Uswah Surabaya, SMPIT At-Taqwa Surabaya, and SMP Darul Quran Surakarta. The research was conducted from 2019 to 2021, precisely before and after the Covid-19 Pandemic. The results showed that the integration of school and family curriculum plays an important role in strengthening student character. Before the Covid-19 pandemic, SMPIT Al Uswah and SMPIT At-Taqwa Surabaya, which were not based on boarding schools, had involved families in student character building. The form of this involvement is providing observation instruments for daily activities such as shalat, tadarus al-quran, fasting on Monday and Thursday, helping parents, and others. The results of observations made by parents will add to the assessment of student affection at the end of each semester. While the integration of the school and family curriculum during the Covid-19 Pandemic is more visible, where in addition to parents being involved in assessing daily non-academic activities, parents also play a role in preparing, facilitating, and accompanying the online teaching and learning process. This can be seen in the implementation of distance learning implemented at SMP Darul Quran Surakarta, which is based on boarding school.